Bahasa Inggris - Aulia Rahma; Sri Ramadhani; Laylan Syavina (Shafin: Sharia Finance and Accounting Journal, 2026)
This investigation seeks to examine the determinants shaping community choices to allocate funds in gold via Islamic financial institutions, utilizing an augmented version of the Theory of Planned Behavior (TPB). Key constructs under scrutiny encompass attitudes toward investment, normative pressures from peers, self-efficacy in behavioral control, financial literacy regarding investments, and perceptions of risk associated with gold assets. Adopting a quantitative methodology, the study relied on survey-based data collection. The target population comprised inhabitants of Medan Baru Subdistrict in Medan Municipality, numbering 36,066 individuals. Sample selection followed the Slovin equation at a 10% error tolerance, yielding 100 participants. Data were gathered primarily via structured questionnaires employing a five-point Likert scale, with subsequent analysis conducted through multiple linear regression in SPSS version 26. Findings reveal that, in isolation, attitudes toward investment and subjective norms exert a statistically significant positive impact on decisions to invest in gold. Conversely, perceived behavioral control, investment acumen, and risk appraisals exhibit no material influence. Collectively, these predictors demonstrate a robust effect on investment intentions (p < 0.001), accounting for 21.2% of the variance (R² = 0.212). These outcomes underscore the preeminence of cognitive orientations and social influences in driving public engagement with gold investments.